Evaluations of Healthcare Providers' Perceived Support From Personal, Hospital, and System Resources: Implications for Well-Being and Management in Healthcare in Montreal, Quebec, During COVID-19. Issue 3 (September 2021) - Lou, Nigel Mantou; Montreuil, Tina; Feldman, Liane S.; Fried, Gerald M.; Lavoie-Tremblay, Mélanie; Bhanji, Farhan; Kennedy, Heather; Kaneva, Pepa; Drouin, Susan; Harley, Jason M.
Increased stressful experiences are pervasive among healthcare providers (HCPs) during the COVID-19 pandemic. Identifying resources that help mitigate stress is critical to maintaining HCPs' well-being. However, to our knowledge, no instrument has systematically examined how different levels of resources help HCPs cope with stress during COVID-19. This cross-sectional study involved 119 HCPs (64 nurses and 55 physicians) and evaluated the perceived availability, utilization, and helpfulness of a list of personal, hospital, and healthcare system resources. Participants also reported on their level of burnout, psychological distress, and intentions to quit. Results revealed that HCPs perceived the most useful personal resource to be family support; the most useful hospital resources were a safe environment, personal protective equipment, and support from colleagues; the most useful system resources were job protection, and clear communication and information about COVID. Moreover, HCPs who perceived having more available hospital resources also reported lower levels of psychological distress symptoms, burnout, and intentions to quit. Finally, although training and counseling services were perceived as useful to reduce stress, training was not perceived as widely available, and counseling services, though reported as being available, were underutilized. This instrument helps identify resources that support HCPs, providing implications for healthcare management.